ARE THE HIGH SERUM INTERLEUKIN-6 AND VASCULAR ENDOTHELIAL GROWTH FACTOR LEVELS AN USEFUL PROGNOSTIC MARKERS IN AGGRESSIVE NON-HODGKIN'S LYMPHOMA PATIENTS? - Hava Üsküdar Teke (Mediterranean Journal of Hematology and Infectious Diseases)
Pro-inflammatory and pro-angiogenic cytokines play an important role in the pathogenesis of lymphoma, as well as recent studies have showed that cytokines can be used as a prognostic marker. NHL patients with high levels of sIL-6 and s-VEGF have poor prognosis and shorter survival. We aimed to determine pre-treatment levels of sIL-6 and s-VEGF, their relation with known prognostic markers and especially IPI levels, and examine their effects on overall survival in newly diagnosed, untreated aggressive NHL patients. Patients with aggressive NHL diagnosis have higher s-VEGF and S-IL-6 levels than healthy population. If particularly sIL-6 levels of patients are above the cut-off levels, the overall survival is shorter. There was no relation between s-VEGF and overall survival time. In addition to the sIL-6 levels, age, ESR, beta-2 microglobulin, WHO performance status and IPI score are independent prognostic factors that are effective especially for overall survival, in clinical follow-up of NHL patients.